PENERAPAN MEDIA LACTORA UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH ANATOMI MAHASISWA PENDIDIKAN JASMANI KESEHATAN DAN REKREASI IKIP BUDI UTOMO MALANG - Afandi, Achmad; Andriani, Ira (JP.JOK (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2018)
This research is a study that aims to improve student learning outcomes in anatomy courses at IkIIP in favor of Utomo Malang. class action research (PTK) which involves repeated reflection consisting of four stages (4 D), namely: planning, action, observation and reflection. Each cycle was conducted two meetings. The results of the study showed that there was an increase in learning outcomes with the use of media Lactora in the subject of motion systems in humans in senior high school VI-A 2017/2018 school year. This can be seen from the average value of the test class I cycle (74.48) with learning completeness (83.87%), indicating an increase compared to before the action with the class average value (60.8) and the learning completeness (38, 71%). Then in the second cycle, the average score of the class increased (83.29) with learning completeness (100%) compared to the results of the first cycle test (74.48%). In the results of this second cycle test all students have completed their study by achieving the specified SKM. The learning process has been proven to improve student learning outcomes.